Institutional logics and regional policy failure: Air pollution as a wicked problem in East African cities. (March 2023) - Andres, Lauren; Bryson, John R; Bakare, Hakeem; Pope, Francis
This paper's conceptual contribution is to highlight the need to place the identification and analysis of institutional logics at the centre of the hybrid framework for policy analysis, with a focus on air pollution as a wicked problem. Different post-structural approaches to policy development have been developed but there is a need to conceptualise and theorise further how different institutions, organisations, and groups, with different institutional logics, contextualise, construct and prioritise wicked problems as policy challenges; additionally, challenges encountered in specific local contexts have to be untangled. Conflicting institutional logics play an important but overlooked role in the analysis of regional policy cycles. This is the first paper to engage in these debates by identifying and exploring the role institutional logics play in conceptualising wicked problems as policy priorities. To do so, it applies and develops post-structuralist approaches to policy analysis developed in education, combined with an institutional logics approach to explore why no effective air quality policy is yet to emerge in East Africa and specifically in Addis Ababa (Ethiopia), Kampala (Uganda) and Nairobi (Kenya). Four contexts of policy formulation and implementation are identified: context of influence, policy formation, implementation and outcomes along with three types of institutional logics: 'science', based on rigor to render societal problems visible; 'influencer', led by NGOs and other stakeholders (e.g. citizens) involved in translating problems to foster awareness and support/fund specific programmes and actions to increase viability; and 'political' linked to decision-making and policy prioritisation. Conflicting institutional logics as we demonstrate can prevent the formulation and implementation of policy solutions.